Right Ventricular Flow Vorticity Relationships With Biventricular Shape in Adult Tetralogy of Fallot - Elsayed, Ayah; Mauger, Charlène A.; Ferdian, Edward; Gilbert, Kathleen; Scadeng, Miriam; Occleshaw, Christopher J.; Lowe, Boris S.; McCulloch, Andrew D.; Omens, Jeffrey H.; Govil, Sachin; Pushparajah, Kuberan; Young, Alistair A. (Frontiers in Cardiovascular Medicine, 2022)
Remodelling in adults with repaired tetralogy of Fallot (rToF) may occur due to chronic pulmonary regurgitation, but may also be related to altered flow patterns, including vortices. We aimed to correlate and quantify relationships between vorticity and ventricular shape derived from atlas-based analysis of biventricular shape. Adult rToF (n=12) patients underwent 4D flow and cine MRI imaging. Vorticity in the RV was computed after noise reduction using a neural network. A biventricular shape atlas built from 95 rToF patients was used to derive principal component modes, which were associated with vorticity and pulmonary regurgitant volume (PRV) using univariate and multivariate linear regression. Univariate analysis showed that indexed PRV correlated with 3 modes (r = -0.55, -0.50 and 0.6, all p<0.05) associated with RV dilatation and an increase in basal bulging, apical bulging and tricuspid annulus tilting with more severe regurgitation, as well as a smaller LV and paradoxical movement of the septum. RV outflow and inflow vorticity were also correlated with these modes. However, total vorticity over the whole RV was correlated with two different modes (r = -0.62, -0.69, both p<0.05). Higher vorticity was associated with both RV and LV shape changes including longer ventricular length, a larger bulge beside the tricuspid valve, and distinct tricuspid tilting. RV flow vorticity was associated with changes in biventricular geometry, distinct from associations with PRV. Flow vorticity may provide additional mechanistic information in rToF remodeling. Both LV and RV shapes are important in rToF RV flow patterns.